Formation of Artistic Historicism in the Early Work of I. I. Lazhechnikov - S. M. Isupova (Научный диалог, 2020)
The article is devoted to the formation of artistic historicism in the work of Lazhechnikov. The relevance of the study is associated with the need for a deeper study of the early work of the writer. It is proved that the foundations of artistic historicism were laid in the early works of Lazhechnikov. It is noted that in the stories “Malinovka” and “Portrait” there is a transformation of sentimental stories with a setting on a historical theme. In the course of the study, the authors of the article conclude that in these works Lazhechnikov does not yet feel the need for historical stylization in the spiritual appearance of the heroes depicted, although he is inclined to preach moral categories, therefore the historicism of these works is of a didactic nature. The “Travel notes of a Russian officer” is also examined in the article. It is noted that in this work the writer’s individual experience becomes a part of historical experience, the accumulation of which is perceived by Lazhechnikov as a process that forms the moral and ethical criteria of the nation. The authors of the article dwell on the fact that the writer creates his own poetics of historical narration, artistic historicism manifests itself in the transfer of historical flavor, in the writer’s reflections on the role of the Russian nation in history. It has been established that Lazhechnikov’s artistic historicism presupposes the interconnection of the past and the present, the comprehension of historical time becomes the basis for the formation of the writer’s historical thinking. The idea is expressed that the historicism of Lazhechnikov’s early works became the basis for the development of the historical theme in the novels of the 1930s.